Identification of Linomide Derivatives as Potential Anticancer Therapeutics using Molecular Docking Studies - Giselle A. Borges e Soares; Tanima Bhattacharya; Tanima Bhattacharya; Shivalingrao Mamledesai; Zhaoquan Ai; Alexandru Madalin Hasan; Simona Cavalu (Frontiers Media S.A., 2022)
12 analogs bearing a structural similarity to Linomide, a bonafide anticancer agent were synthesized wherein cyclization of substituted dianilides rendered 4-hydroxyquinolin-2(1H)-ones that were subjected to a Mannich reaction to yield 4-hydroxy-3-(substituted-1-ylmethyl) quinolin-2(1H)-one analogs. Characterization was performed using IR, 1H nuclear magnetic resonance and 13C NMR spectral analysis. Subsequently, in vitro anticancer studies revealed that Compound 4b showed maximum cytotoxicity with IC50 values of 1.539 μM/ml and 1.732 μM/ml against A549 and K562 cell lines respectively. This, however, is lower in comparison with standard Paclitaxel (IC50 values of 0.3 μM/ml for both cell lines). Surprisingly, docking studies at the active site of EGFRK revealed Compound 4b possessed a MolDock Score of -110.2253 that is highly comparable to the standard 4-anilinoquinazoline (MolDock Score of -112.04). Our computational and biological data thus provides an insight on the cytotoxicity of these derivatives and warrants future research that can possibly lead to the development of potent anticancer therapeutics.